EATING DISORDER AND DEPRESSION AMONG PUBLIC SERVANTS IN AKWA IBOM STATE, NIGERIA - Petters, Janet S; Akaninyene Umo, Udeme (International Journal of Research -GRANTHAALAYAH, 2020)
This study was carried out to establish the relationship between eating disorder and depression among public servants in Akwa Ibom State, Nigeria. The study adopted the expost facto design. The sample consisted of 1000 (533 males, 467 females) public servants who were randomly selected from state ministries, schools, boards and parastatals in the state. A Public Servant Opinion Questionnaire (PSOQ) constructed by the researcher was used for data collection. A null hypothesis was tested in the study using the Pearson Product Moment Correlation Coefficient. This paper also highlights some causes and mechanisms of eating disorder and depression, biological or genetic factors and addiction. The major findings indicated that eating disorder significantly led to some degree of depression, which is a mental illness. Based on this result, it was concluded that eating disorder was a significant factor in explaining the incidence of depression. The major recommendations are that depressed people should be referred to seek the services of social psychologists, psychotherapists, and clinical psychologists in psychiatric hospitals, and also that, government should help in providing good working conditions for her staff.